Reconstructing Native American population history - Reich, David; Patterson, Nick; Campbell, Desmond; Tandon, Arti; Mazieres, Stéphane; Ray, Nicolas; Parra, Maria V.; Rojas, Winston; Duque, Constanza; Mesa, Natalia; García, Luis F.; Triana, Omar; et al. (Nature (London), 2012)
A survey of genetic variation in Native American and Siberian populations reveals that Native Americans are descended from at least three streams of gene flow from Asia: after the initial peopling of the continent there was a southward expansion facilitated by the coast, with sequential population splits and little gene flow after divergence, especially in South America. The roads to the Americas The settlement of the Americas occurred at least 15,000 years ago by means of the Beringia land bridge that existed between Asia and America during the ice ages. Key questions about how many migrations were involved and subsequent dispersal patterns within the Americas remain unresolved. This new survey of genetic variation in Native American and Siberian populations shows that Native Americans descend from at least three waves of migration from Asia. After the initial peopling of the continent there was a southward expansion along the coast, with sequential population splits and little gene flow after divergence, particularly in South America. The peopling of the Americas has been the subject of extensive genetic, archaeological and linguistic research; however, central questions remain unresolved 1 , 2 , 3 , 4 , 5 . One contentious issue is whether the settlement occurred by means of a single 6 , 7 , 8 migration or multiple streams of migration from Siberia 9 , 10 , 11 , 12 , 13 , 14 , 15 . The pattern of dispersals within the Americas is also poorly understood. To address these questions at a higher resolution than was previously possible, we assembled data from 52 Native American and 17 Siberian groups genotyped at 364,470 single nucleotide polymorphisms. Here we show that Native Americans descend from at least three streams of Asian gene flow. Most descend entirely from a single ancestral population that we call ‘First American’. However, speakers of Eskimo–Aleut languages from the Arctic inherit almost half their ancestry from a second stream of Asian gene flow, and the Na-Dene-speaking Chipewyan from Canada inherit roughly one-tenth of their ancestry from a third stream. We show that the initial peopling followed a southward expansion facilitated by the coast, with sequential population splits and little gene flow after divergence, especially in South America. A major exception is in Chibchan speakers on both sides of the Panama isthmus, who have ancestry from both North and South America.